(untitled) (Cadernos de Sociomuseologia, 2020)
Abstract: This work aimed at discussing the association made between the anthropological concept of culture and the broadening of the scope of the notion of heritage that has occurred since the beginning of the 21st century, specifically with regard to the policies established for the protection of intangible cultural heritage. It has been argued that because it is polysemic, the anthropological concept of culture had been related to the notion of heritage since the first quarter of the 20th century, that is, almost a century before. What has changed is the meaning attributed to both categories. In addition, it was discussed that an expansion of the heritage category is the result of the action of the most diverse social actors in the demand for differential cultural rights, operating with a specific political-cultural grammar, which dynamized enunciations such as multiculturalism, cultural diversity and representation, seeking a non-hierarchical vision of culture, which directly impacted on the conceptualization of heritage and the policy of protection of cultural goods. To this end, as a way of delimiting the discussion, it was decided to work with documents produced by the United Nations Educational, Scientific and Cultural Organization (UNESCO) in the period, since it is a protagonist agent and arena with regard to policies for the protection of cultural goods. Keywords: heritage, anthropological concept of culture, immaterial heritage, cultural diversity.